Looking Both Ways: The Intersection of Road Safety Education and Early Childhood Research. Issue 1 (March 2014) - Waters, Stacey; Baker, Samantha; Bruce, Kaashifah; Lindner, Helen; Clarkson, Emma
THE EARLY YEARS ARE a critical time to introduce key concepts for lifelong learning. In recognition of this, in July 2009, the Council of Australian Governments (COAG) endorsed Australia's first strategy outlining a vision for the development of young children and the implementation of the Early Years Learning Framework (EYLF). Road safety education is an important component of early childhood education as it lays the foundation for children to become safe road users. Therefore, to provide early childhood educators with a framework for evidence-based road safety education, VicRoads on behalf of the Road Safety Education Reference Group Australasia (RSERGA), commissioned the development of National Practices for Early Childhood Road Safety Education. This article outlines the development of these practices. It is anticipated the engagement by educators with the National Practices for Early Childhood Road Safety Education will foster early childhood road safety learning; however, future research is required to trial and evaluate these practices.